SPATIAL VARIABILITY AND GEOSTATISTICAL ANALYSIS OF SOIL FERTILITY INDICATORS IN GUSAU LOCAL GOVERNMENT AREA, ZAMFARA STATE, NIGERIA - Abdulmuddalib, Muhammad Auwal; Salihu, Ardo Musa; Abubakar, Muhammad Tahir; Usman, Bapetel; Solomon, Ibrahim Rejoice (FUDMA JOURNAL OF SCIENCES, 2026)
Soil fertility variability reveal a significant challenge to sustainable agriculture in tropical agroecosystems, particularly in sub-Saharan Africa. This study evaluated the spatial variability and geostatistical characteristics of soil fertility indicators in Gusau, Zamfara State, Nigeria. Using a systematic sampling approach across Wanke and Magami, 80 surface soil samples (0–20 cm) were analyzed for pH, organic carbon (OC), total nitrogen (TN), available phosphorus (AVP), exchangeable potassium (K), and cation exchange capacity (CEC). Descriptive statistics revealed low variability in pH, moderate variability in OC and K, and high variability in AVP, indicating pronounced spatial heterogeneity. Pearson correlation analysis showed weak to moderate relationships among properties, with OC and CEC emerging as primary drivers of nutrient dynamics. Regression analysis confirmed OC and CEC as significant predictors of soil fertility status (p < 0.001). Geostatistical analysis, employing semivariogram modeling and ordinary kriging, demonstrated moderate spatial dependence for most properties and revealed distinct spatial patterns across the landscape. Spatial distribution maps characterized the area as having slightly acidic soils, moderate OC, and adequate K availability, but widespread AVP deficiency. These findings underscore the necessity of site-specific nutrient management and the pivotal role of organic matter in stabilizing soil fertility. To enhance agricultural productivity and sustainability in the Sudan savanna region, the study recommends integrated soil fertility management practices, specifically prioritizing organic amendments and targeted phosphorus fertilization to address identified deficiencies. This research provides a critical and comprehensive framework for precision nutrient application to mitigate the negative effects of uneven soil conditions in northern Nigerian agroecosystems.
Keywords: Spatial variability; geostatistics; Soil fertility indicators; Available phosphorus; Soil organic carbon